THE CONCEPT OF THE INJURED PARTY AND THE VICTIM OF A CRIMINAL OFFENSE AS CRIMINAL PROCEDURAL SUBJECTS - Milojević, Marija (Glasnik Advokatske komore Vojvodine, 2026)
The paper analyzes the concept of the criminal procedure subject through theoretical, normative, and comparative perspectives, with a special focus on the position of the injured party and the victim of a criminal offense within criminal proceedings. It begins with the traditional understanding that criminal procedure subjects are bearers of specific procedural functions—adjudication, prosecution, and defense—and classifies them as principal or secondary subjects. Within this framework, the injured party is defined as a secondary procedural subject but with a complex procedural status, as they may simultaneously perform multiple functions (e.g., testifying, initiating prosecution, or submitting a property claim). Special attention is devoted to distinguishing between the concepts of the injured party and the victim of a criminal offense in domestic legislation and international instruments, particularly the EU Directive 2012/29/EU and the 1985 UN Declaration of Basic Principles of Justice for Victims of Crime and Abuse of Power. The analysis demonstrates that the notion of a victim encompasses a broader range of rights, including extraprocedural protection, support, and assistance, thereby transcending the traditional procedural framework of the injured party. The paper concludes that harmonizing domestic law with international standards requires either normative recognition of the victim as a distinct procedural subject or the expansion of the existing concept of the injured party, while maintaining the adversarial nature of criminal proceedings and ensuring effective victim protection both within and beyond their formal scope